THE INFLUENCE OF PARTICIPATORY BUDGETING, CLARITY OF BUDGET TARGETS, AND INTERNAL CONTROL ON MANAGERIAL PERFORMANCE IN THE MODERATION OF ORGANIZATIONAL COMMITMENT TO REGIONAL APPARATUS ORGANIZATIONS (OPD) IN KEDIRI CITY - Meilinda Trinita Sari; Linawati; Erna Puspita (INJOSEDU: International Journal of Social and Education, 2025)
This research is motivated by the suboptimal realization of program and activity budgets in Regional Apparatus Organizations (OPD) in Kediri City, even though the average performance achievement reaches 87%. This indicates that the budget is not optimally absorbed, which can be caused by a lack of participation in budgeting, unclear budget targets, and weak internal control. This study aims to analyze the influence of participatory budgeting, clarity of budget goals, and internal control on managerial performance, as well as examine the role of organizational commitment as a moderation variable. The method used is a quantitative approach with probability sampling techniques and a sample of 50 respondents. Data analysis was carried out using multiple linear regression with Moderating Regression Analysis (MRA) supported by classical assumption test and hypothesis test through SPSS software version 30. The results showed that participatory budgeting had no significant effect on managerial performance, while clarity of budget goals and internal control had a significant effect. Organizational commitment has been proven not to moderate the influence of participatory budgeting, but to moderate the influence of the clarity of budget goals and internal control on managerial performance. These findings confirm the importance of clarity of goals and effective controls, especially with the support of strong organizational commitments.